Platelet Inhibitory Effect of Clopidogrel in Patients Treated With Omeprazole, Pantoprazole, and Famotidine: A Prospective, Randomized, Crossover Study. Issue 6 (29th April 2013) - Arbel, Yaron; Birati, Edo Y.; Finkelstein, Ariel; Halkin, Amir; Kletzel, Hanna; Abramowitz, Yigal; Berliner, Shlomo; Deutsch, Varda; Herz, Itzhak; Keren, Gad; Banai, Shmuel
Abstract Background Concerns about an inhibitory effect of proton pump inhibitors (PPIs) on clopidogrel metabolism have been raised. Because the pharmacological effect of clopidogrel is dependent on genetically determined activity of the hepatic cytochrome P450 isoenzymes system, it is important to examine the interaction between different PPIs and high on‐treatment platelet reactivity (HPR) after controlling for genetic variability. The aim of the study was to assess the effect of 2 PPIs and a histamine‐2 (H2) receptor‐blocker on platelet reactivity in a crossover trial where each patient was alternately treated with each drug. Hypothesis Omeprazole reduces HPR more than other PPI or H2 blockers. Methods Patients treated with aspirin and clopidogrel for at least 1 month were assigned to 3 consecutive 1‐month treatment periods during which they were treated with each of the 3 study medications twice daily: omeprazole 20 mg, famotidine 40 mg, and pantoprazole 20 mg. At the end of each treatment phase, platelet function was evaluated with the Verify Now system using 2 cutoff values (>208 P2Y12 reaction units [PRUs] and >230 PRUs) for the definition of HPR. Results Patients with HPR were older than those without HPR (62 ± 10 vs 55 ± 8 years, respectively, P = 0.03). HPR was more prevalent during omeprazole therapy compared to famotidine or pantoprazole (48%, 33%, and 31%, respectively, for the 208 PRU cutoff, P= 0.04; and 37%, 17%, and 23%, respectively, for the 230 PRU cutoff, P= 0.003). Conclusions After eliminating the effects of interindividual variability in clopidogrel metabolism, omeprazole therapy was associated with substantially more HPR than famotidine or pantoprazole.